KEMULIAAN DAN PERGESERAN MAKNA GURU - Yasa, Putu Dana (PANGKAJA: JURNAL AGAMA HINDU, 2021)
A teacher has a very important role and responsibility for change and improving the quality of students. The responsibility of a teacher must be believed and realized so that the teacher really gives true knowledge in the teaching process. The Hindu view in understanding the meaning of the word "guru" is not limited to a profession as a teaching staff, but in Hindu theological studies "guru" is a person who has a very noble character and position. The glory of a "guru" is contained in various Hindu literature which is also used as a source for Hindus in their efforts to understand religious teachings. "guru" is not just a profession but a person who has spiritual qualifications who are able to lead his students to have ethics and morals. A true "guru" will not be bound by material shackles and even has to be free from everything that is materialism.